2020
DOI: 10.1111/pce.13977
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the physiological relevance of sucrose export repression by an Flowering Time homolog in the long‐distance phloem of potato

Abstract: Yield of harvestable plant organs depends on photosynthetic assimilate production in source leaves, long‐distance sucrose transport and sink‐strength. While photosynthesis optimization has received considerable interest for optimizing plant yield, the potential for improving long‐distance sucrose transport has received far less attention. Interestingly, a recent potato study demonstrates that the tuberigen StSP6A binds to and reduces activity of the StSWEET11 sucrose exporter. While the study suggested that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…SWEET-transporter kinetics are the bottleneck in this step, we therefore parameterized this step with SWEET-specific parameters. Expected differences between SWEET and SUT-transporters facilitating uptake in the parenchyma are small (van den Herik et al, 2021). SWEET rates were reported as 39 ± 6 pmol/oocyte/min (Chen et al, 2012), which was rewritten to 0.9e-19 mol/μm 2 /s by using reported oocyte dimensions (Wallace & Selman, 1981).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SWEET-transporter kinetics are the bottleneck in this step, we therefore parameterized this step with SWEET-specific parameters. Expected differences between SWEET and SUT-transporters facilitating uptake in the parenchyma are small (van den Herik et al, 2021). SWEET rates were reported as 39 ± 6 pmol/oocyte/min (Chen et al, 2012), which was rewritten to 0.9e-19 mol/μm 2 /s by using reported oocyte dimensions (Wallace & Selman, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…In potato, the tuberigen StSP6A induces tuber onset (Navarro et al, 2011) which is a major developmental transition, associated with large changes in plant physiology among which is the emergence of a new, and strong, sucrose sink. Besides its role in tuber establishment by switching on the tuber developmental program, StSP6A was shown to inhibit sucrose export from the phloem to the apoplast through inhibition of SWEET-transporters (Abelenda et al, 2019) thereby enhancing the efficiency of sucrose delivery to sink tissues (van den Herik et al, 2021). Using a biophysical model of sugar and water transport we recently demonstrated that this dual role of StSP6A , tuber induction and inhibition of SWEET-mediated export, preferentially enhances sucrose allocation to the tuber sink (van den Herik & ten Tusscher, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, sucrose delivery to tubers is substantially increased at the cost of other plant organs (Fernie et al, 2020). StSP6A, the tuberigen, affects tuberization and sucrose delivery through initiation of tuber formation (Navarro et al, 2011) as well as increasing the relative efficiency of resource allocation towards tubers by mitigation of sucrose efflux via the sucrose exporter l., h StSWEET11 in the long-distance phloem (Abelenda et al, 2019;van den Herik et al, 2021;van den Herik & ten Tusscher, 2022). Tuberization is further under control of environmental conditions (such as light, temperature, water availability and soil nutrient levels), hormone levels and sucrose availability.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Importantly, both polymer-trap loaders and plants producing sugar alcohols translocate significant amount of sucrose in parallel to the aforementioned special sugars. 30 , 31 , 32
Figure 1 B. tabaci adults can sense, discriminate, and choose between different concentrations of sucrose (A) The B. tabaci stylets encounter increasing apoplastic sucrose concentrations 33 , 34 , 35 on their way to the phloem sieve elements located deep within the leaf. Sucrose concentrations in the phloem sap are from Hayashi and Chino and Fink et al.
…”
Section: Introductionmentioning
confidence: 99%
“… (A) The B. tabaci stylets encounter increasing apoplastic sucrose concentrations 33 , 34 , 35 on their way to the phloem sieve elements located deep within the leaf. Sucrose concentrations in the phloem sap are from Hayashi and Chino and Fink et al.…”
Section: Introductionmentioning
confidence: 99%